USING SMALL GROUP DISCUSSION TO IMPROVE STUDENTS’ READING ACHIEVEMENT ON NARRATIVE TEXT - Arisman, Rizal; Haryanti, Irda Sriyanti (Universitas Muhammadiyah Palembang, 2019)
Objective of this research was to find out significant difference of reading achievement between students who are taught using Small Group Discussion and those are taught using conventional method. The research used quantitative approach by applying quasi experimental design of nonequivalent group design. Population of this research was the grade eight students of SMP Negeri 2 Pasarwajo in school year of 2017/2018. Number of populations were 118 students. Samples of this research were class VIII.A as experimental class which consisted of 30 students and VIII.B as the control class which consisted of 29 students. Instrument of this research was test and it was analyzed using Independent Sample T Test. This research concludes that there was a significant difference of reading achievement between the class whom is taught by using Small Group Discussion method and the class whom is taught by using conventional method.